BASIC FOUNDATIONAL PREREQUISITES FOR FORMING EFFECTIVE EMPLOYMENT IN ECONOMIC SYSTEMS FOR INCLUSIVE ECONOMIC GROWTH - Ziankova, I.U. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Ėkonomika, 2017)
At the moment, the theoretical and methodological foundations for achieving full and effective employment have not been fully studied by scientists, and the fundamental prerequisites for ensuring economic growth have not been systematized. The relevance of the research is proved by analyzed practical basis for the formation of employment in context of countries with grounded economic indicators: labor productivity, GDP dynamics. The aim of the research is to develop the theoretical and methodological foundations for effective employment of the population on the basis of the genesis of the fundamental prerequisites for the formation of effective employment for inclusive economic growth. The novelty of this research is that the fundamental prerequisites for the formation of effective employment have been studied and scientifically grounded. The author comes to the conclusion that when forming effective employment it is important to take into account the coordinated development of the labor market and market of educational services; interaction of the labor force’s skill level and the elasticity of demand for labor resources by the level of wages; correlative interaction of labor productivity in the workplace, in the household and the life cycle of a person; the relationship between the degree of elasticity of the supply of female labor and the level of wages, between the number of children in a family and their age; the conjugation of the workforce with the company’s objectives, the policy of forming the level of wages, the coefficient of labor participation; institutional rules on the labor market, which complement the market laws operation.